Drug Information- A Brief Introduction on Drug Information Agencies in Nepal - Sharma, Surya Raj; Shrestha, Bimal M; Bhuju, Gajendra B (Medical Journal of Shree Birendra Hospital, 2001)
Drug Information- A Brief Introduction on Drug Information Agencies in Nepal